PLANT GROWTH STIMULATION OF LIGNITE HuMIC ACID PART-II EFFECT oF LIG NITE DERIVED AMMONIUM HUMATE ON WHEAT ( TRITICUM AESTIVUM-V )C ROP USING DIFFERENT LEVELS OF PHOSPHATE FERTILIZER (Biological Sciences - PJSIR, 2002)
The effect of humic acids (ammonium humate) derived from Pakistani lignite on the growth and grain yield of wheat  (I'rzticum aeshvum-V) crop m the presence and absence of phosphate fertilizer and in combination with various levels of phsphate fertilizer was studied. Application of humic acids in all doses  when  applied  alone  and  in  combination  with vanous levels of phosphate fertilizer (TSP) has significant beneficial effect on the growth and yield of wheat. An enhanced effect  on the growth  and  grain yield  was notified  when  Humic  acids was added  alone without using any fertilizer.